Accuracy of Transnasal Cannulation and Dilation of the Maxillary Ostium in Cadavers with Intact Uncinates. Issue 1 (January 2013) - Brodner, David; Alexander, Ian; Chandler, Stephen; Cutler, Jeffrey; Saigal, Kapil
Background: Transnasal cannulation of the natural ostium in patients with an intact uncinate process is complicated by the lack of direct visualization of the ostium. Accuracy of transnasal dilation of the maxillary ostium was evaluated for a malleable-tipped balloon device that was bent to specific angles for avoiding the fontanelle during cannulation. Methods: Transnasal cannulation and dilation of 42 cadaver maxillary sinus ostia was attempted by 6 surgeons including 3 with very limited clinical experience using the study device. All physicians received procedure training including the technique to shape the balloon device into the recommended 135° maxillary configuration. Tissue dissection was prohibited. Canine fossa trephination and transantral endoscopy were used to evaluate cannulation and dilation outcomes. Physician operators were blinded to transantral images and results were documented by two observers. Results: Appropriate transnasal cannulation and dilation of natural maxillary sinus ostia occurred in 92.9% (39/42) of attempts. Two failures emanated from procedural deviations. In one deviation, the bend angle was changed to 90° and the device tip did not cannulate the ostium. In the second, the device was passed through a preexisting hole in the uncinate and cannulated the natural ostium. A third failure occurred when the device was passed through the fontanelle creating a false lumen. Conclusion: Using recommended procedural techniques and a malleable-tipped balloon device, newly trained and experienced physicians alike can perform uncinate-preserving transnasal cannulation and dilation of the maxillary ostium with a high rate of success.